Cost-effectiveness of using protons for breast irradiation aiming at minimizing cardiotoxicity: A risk-stratification analysis - Li, Guo; Xia, Yun-Fei; Huang, Yi-Xiang; Okat, Deniz; Qiu, Bo; Doyen, Jerome; Bondiau, Pierre-Yves; Benezery, Karen; Gao, Jin; Qian, Chao-Nan (Frontiers in Medicine, 2022)
Background Incidental exposure of the heart to ionizing irradiation is associated with an increased risk of ischemic heart disease and subsequent fatality in patients with breast cancer after radiotherapy. Proton beam therapy can limit the heart dose in breast irradiation to a negligible level. However, compared with conventional photon modality, proton breast irradiation is more expensive. In this study, we performed cost-effectiveness analyses to identify the type of patients who would be more suitable for protons. Methods A Markov decision model was designed to evaluate the cost-effectiveness of protons vs. photons in reducing the risk of irradiation-related ischemic heart disease. A baseline evaluation was performed on a 50-year-old woman patient without the preexisting cardiac risk factor. Furthermore, risk-stratification analyses for photon mean heart dose and preexisting cardiac risk were conducted on 40-, 50-, and 60-year-old women patients under different proton cost and willingness-to-pay (WTP) settings. Results Using the baseline settings, the incremental effectiveness (protons vs. photons) increased from 0.043 quality-adjusted life-year (QALY) to 0.964 QALY when preexisting cardiac risk increased to 10 times its baseline level. At a proton cost of 50,000 US dollars ($), protons could be cost-effective for ≤ 60-year-old patients with diabetes and ≤50-year-old patients with grade II–III hypertension at the WTP of China ($37,653/QALY); for ≤ 60-year-old patients with diabetes and ≤ 50-year-old patients with grade II–III hypertension or ≥ 2 major cardiac risk factors at a WTP of $50,000/QALY; and for ≤ 60-year-old patients with diabetes, grade II–III hypertension or ≥ 2 major cardiac risk factors and ≤ 50-year-old patients with total cholesterol ≥ 240 mg/dL at a WTP of $100,000/QALY. Conclusion Patients' preexisting cardiac risk status was a key factor affecting the cardiac benefits gained from protons and should therefore be a major consideration for the clinical decision of using protons; cost-effective scenarios of protons exist in those patients with high risk of developing cardiac diseases.